(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
Innovative technologies in clinical anatomy play a key role in the modernization of medical education and clinical practice. The relevance of this topic is обусловлена the rapid development of minimally invasive and robotic surgery, the need for high diagnostic accuracy, and the implementation of a personalized approach to patient treatment.